Dietary Intakes and Nutritional Status of Mother-Child (6-23 Months Old) Pair Targeted through the "Organic Residual Products for Biofortified Foods for Africa Project" in Rural Area in Senegal - Thiam, Mbeugué; Diouf, Adama; Coly, Ousseynou Baba; Kébé, Saliou Diombo; Diongue, Ousmane; Badiane, Abdou; Faye, Mane Hélène; Doudou Sylla, Papa Mamadou Dit; Idohou-Dossou, Nicole; Medoc, Jean Michel (International Journal of Child Health and Nutrition, 2022)
Background: Despite micronutrient supplementation and food fortification strategies carried out for decades, micronutrient deficiencies remain prevalent among children under 5 years old in rural area in Senegal. The OR4FOOD project was implemented as a preventive and long-term approach to reduce malnutrition through biofortification. Objective: We aimed to assess the baseline dietary intakes and nutritional status of the mother-child (6-23 months old) pair in a rural community in Senegal. Methods: Dietary intakes were assessed using dietary recall questionnaires and weight food records. All foods and beverages consumed from waking to bedtime were quantified, and nutrient intakes were calculated. The nutritional status was measured by anthropometry. Results: Results showed that 77.2% of children had low dietary diversity score. Only 18% of them received an appropriate complementary feeding according to the minimum acceptable diet. Cereals and legumes were among the most consumed food groups, whereas orange-fleshed sweet potato (OFSP) and animal food products were rarely consumed. Median dietary intakes of iron, zinc, and vitamin A were lower than the recommended dietary allowances. Acute malnutrition and stunting affected 14.6% and 16.9% of children, respectively. Overall, 20.8% of mothers were underweighted, and overweight/obesity affected 23.1% of them. Conclusion: Malnutrition remains prevalent in rural areas of Senegal and affects both mothers and children. Furthermore, their nutrient requirements were not covered by the diet. Millet and cowpea being widely consumed, optimizing their iron and zinc content through biofortification and the introduction of OFSP might improve micronutrient intakes and would be promising strategies to prevent child malnutrition.